Primary Commodities : May 1987. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1987)
This paper provides an analysis of recent developments relating to the major nonfuel primary commodities entering international trade. Particular attention is given to market price movements in 1986 and to the factors underlying these movements. In the case of some agricultural markets, changes in commodity-specific policies of industrial countries have also had the effect of increasing supplies and competition for markets. The other factors, including rates of inflation, exchange rate changes, and interest rates, have also influenced commodity prices, at least when measured in nominal dollar terms. The evolution of economic activity in the industrial countries is most relevant in explaining movements in prices of metals and other raw materials used in industry, while movements in prices of food and beverages are better explained by supply factors. Changes in production capacity resulting from investment decisions made in earlier years can have an important influence on commodity prices.